Simple Kirkman packing designs SKPD({3,5*}, v) with index two - Cao H., (Utilitas Mathematica, 2008)
A simple Kirkman packing design SKPD({w,s*},v) with index λ is a resolvable packing with distinct blocks and maximum possible number of parallel classes, each containing one block of size s and all other blocks of size w, such that each pair of distinct elements occurs in at most λ blocks. This article investigates the spectra of simple Kirkman packing designs SKPD({3,5*},v) with index 2.